Ultra-wide band antenna designs and numerical system modelling for forward-looking GPR - Turk, Ahmet Serdar; Aksoy, Serkan; Keskin, Ahmet Kenan; Senturk, Mustafa Dagcan; Caliskan, Alper; Ozakin, Mehmet Burak (WILEY, 2015)
This paper presents ultra-wide band (UWB) horn feeder and parabolic reflector antenna designs, which are considered highly suitable for forward-looking vehicle-mounted ground-penetrating radar (GPR) systems and time-domain numerical modelling of impulse GPR signal radiation, wave propagation and target scattering. In this context, the partial dielectric-loaded Vivaldi shaped TEM horn (PDVA), TEM horn fed double-ridged horn (PDTEM-RHA) and their compact versions are investigated, designed simulated and measured. An offset parabolic reflector antenna prototype with a compact PDTEM-RHA feeder is proposed to reach hyper-wide band impulse radiation performances from 500 MHz up to 15 GHz for a multi-band forward-looking GPR operation that can provide deep subsurface detection with high-resolution imaging, due to a big advantage of narrowed beam widths. The antenna gain and radiation pattern performances are demonstrated with measurement results.
Keywords: Geochemistry & Geophysics